2020
DOI: 10.1007/s12028-020-01029-8
|View full text |Cite
|
Sign up to set email alerts
|

Mechanical Ventilation, Sedation and Neuromonitoring of Patients with Aneurysmal Subarachnoid Hemorrhage in Germany: Results of a Nationwide Survey

Abstract: Objective: Current evidence-based guidelines for the management of aneurysmal subarachnoid hemorrhage (aSAH) focus primarily on timing, modality and technique of aneurysm occlusion, and on prevention and treatment of delayed cerebral ischemia. Significant aspects of management in the intensive care unit (ICU) during the later course of aSAH such as ventilation and sedation (VST) remain unaddressed. aSAH patients present unique challenges not accounted for in general ICU recommendations and guidelines, which is… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
1
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 29 publications
0
10
1
1
Order By: Relevance
“…However, data to date have suggested that patients with ICH and COVID-19 present with lower systolic blood pressure, relative to spontaneous ICH. 14 Furthermore, ACE2 dysregulation may also contribute to the post-ischemic inflammation cascade through the accumulation of angiotensin 2, resulting in decreased perfusion in the ischemic zone and the development of larger infarct volumes. 15,16 The impaired endothelial function in cerebral arteries caused by ACE2 inactivation has also been implicated in the pathogenesis of cerebrovascular events, including both ischemic and hemorrhagic stroke.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, data to date have suggested that patients with ICH and COVID-19 present with lower systolic blood pressure, relative to spontaneous ICH. 14 Furthermore, ACE2 dysregulation may also contribute to the post-ischemic inflammation cascade through the accumulation of angiotensin 2, resulting in decreased perfusion in the ischemic zone and the development of larger infarct volumes. 15,16 The impaired endothelial function in cerebral arteries caused by ACE2 inactivation has also been implicated in the pathogenesis of cerebrovascular events, including both ischemic and hemorrhagic stroke.…”
Section: Resultsmentioning
confidence: 99%
“…Cerebral hemorrhage. Several case reports and cohort studies have recently been published presenting COVID-19 patients with parenchymal hemorrhage, 58,59,[79][80][81][82][83][84][85] subarachnoid hemorrhage, 14,58,59,86 and subdural hematoma. 59 A retrospective case series of five patients showed that COVID-19 patients with ICH were younger than expected and mostly suffered from lobar ICH.…”
Section: Ischemic Strokementioning
confidence: 99%
“…The authors found that the relative risk of stroke in the group of patients with COVID-19 was 8.1 (95% CI 2.5-26.6), as compared with 4.6 (95% CI 1.4-15.7) in the reference group [5]. This study is of great interest, as the authors took into account the infl uence of infection COVID-19 show lower values for systolic BP than patients without COVID-19 [17], which requires further investigation. Impairment to the operation of ACER2 receptors promotes triggering of the postischemic infl ammatory cascade due to accumulation of angiotensin 2, which has nothing to bind to, which in turn exacerbates hypoperfusion in the cerebral ischemia zone and promotes expansion of the volume of cerebral infarct [18].…”
mentioning
confidence: 76%
“…There are lacking standards regarding ventilation-, monitoring- and sedation-management after aneurysmal SAH, which are also assumed to have effects on the outcome [ 45 ]. With the help of a questionnaire ICU practices in aneurysmal SAH in Germany were evaluated and compared to guidelines, if existing.…”
Section: Discussionmentioning
confidence: 99%
“…In this study, ICU management after aneurysmal SAH was found to be very heterogeneous. This leads to the conclusion, that evidence in this area of SAH-management is insufficient [ 45 ]. There is a necessity to define optimal requirements and guidelines of ICU management after SAH, particularly management of ventilation, timing of tracheostomy, sedation and intracranial pressure (ICP) / cerebral metabolism monitoring.…”
Section: Discussionmentioning
confidence: 99%